Overview Of Toddlers Diarrhea Self-Medication At Pharmacy “X”, Sidoarjo, January-March 2025 - Ach Zakyah Al Fauzi; Andri Priyoherianto; Lailatus Sholihah (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Diarrhea is one of the common health problems in toddlers and is often treated through self-medication by the community. Choosing the right medicine is very important to avoid complications, considering the low immune system of toddlers and the potential risks of using drugs without a doctor's prescription. This study used a qualitative descriptive design, the study was conducted at the